(untitled) - Dore, Ronald (Stanford, Calif., 1987)
Content: The interprise and income determination; The linking institutions
Keywords: Industries,Công nghiệp; Industrial policy,Chính sách công nghiệp; Japan,Kinh tế Nhật Bản